Single Cell RNA Sequencing Identifies a Unique Inflammatory Macrophage Subset as a Druggable Target for Alleviating Acute Kidney Injury (Adv. Sci. 12/2022). Issue 12 (25th April 2022) - Yao, Weijian; Chen, Ying; Li, Zehua; Ji, Jing; You, Abin; Jin, Shanzhao; Ma, Yuan; Zhao, Youlu; Wang, Jinwei; Qu, Lei; Wang, Hui; Xiang, Chengang; et al.
Abstract : Alleviating Acute Kidney Injury In article number 2103675, Ying Chen, Fan Bai, Li Yang, and co‐workers revealed S100a8/a9 high infiltrated macrophage initiated and amplified inflammation in acute kidney injury. The "Comets" represent S100a8/a9 high infiltrated macrophages which derive from bone marrow, response the earliest to the signals sent by the injured kidney, infiltrate and cause further damage to the kidney (the kidney with flame). Two small molecule drugs (little cartoon people in light or dark blue color) which specifically inhibit S100a8/a9, could reduce renal inflammation and protect kidney from acute injury (the kidney without flame).